2014
DOI: 10.3892/ol.2014.2340
|View full text |Cite
|
Sign up to set email alerts
|

Primary cerebellar endodermal sinus tumor: A case report

Abstract: Endodermal sinus tumors are rare malignant germ cell tumors that usually originate from the gonads and are rarely observed extragonadally. Pure primary endodermal sinus tumors of the cerebellar hemisphere are extremely rare and patients diagnosed with the disease often have a poor prognosis. The symptoms of YSTs are unspecific and associated with the location of tumors. Intracranial YSTs (such as cerebellar hemispheres) always present with symptoms including headache and poor vision. The present study reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…YST is typically a well-defined round or oval tumor with isointense T1-weighted images and slightly hyperintense T2-weighted images (2, 3). After gadolinium injection, the tumor has strong homogenous enhancement (2,3). The imaging findings of our patient were consistent with those in previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…YST is typically a well-defined round or oval tumor with isointense T1-weighted images and slightly hyperintense T2-weighted images (2, 3). After gadolinium injection, the tumor has strong homogenous enhancement (2,3). The imaging findings of our patient were consistent with those in previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…It has been confirmed that the significant increase of AFP level in serum and cerebrospinal fluid is related to YST (3,4). Initially, our case was not considered to be primary YST because it was consistent with medulloblastoma, given the age distribution and due to the rarity of YST in the cerebellar hemisphere.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The anterior third ventricle Yes No Yes Alive 2014 [14] M 3 Left cerebellar hemisphere Yes No No 6 2013 [15] F 17 Bilateral basal ganglia Yes Yes Yes Alive 2013 [16] M 4 Posterior fossa Yes Yes Yes 60 2013 [17] M 2.5 Posterior fossa Yes Yes Yes Alive 2012 [18] F 15 Pineal region, the right lateral ventricle Yes Yes Yes NR 2011 [19] M 13 Right basal ganglia No Yes Yes 21 2011 [20] M 2 Left temporoparietal lobe Yes No No 36 2011 [5] M recurrence, and it is recommended that patients receive intensive chemotherapy. [33] In our case, the serum AFP level dropped constantly to the normal range during the 8 cycles of EP chemotherapy (Fig.…”
Section: Discussionmentioning
confidence: 99%